Financing innovative start-ups in Portuguese context: what is the role of business angels networks? - Bilau, José (2017)
Business angels provide both financing and managerial experience, which increase the likelihood of the survival of innovative start-ups. Over the last years, European countries with developing informal venture capital markets have seen governments support the creation of business angels networks (BANs) to increase and consolidate these markets. Using the Portuguese context to carry out the empirical work, this paper provides an assessment of value added provided by angels’ networks. A total of 88 useable responses were received and analysed using non-parametric statistical techniques. This paper demonstrates that is evidence of positive contribution of BANs in terms of bringing together investors and linking them with entrepreneur’s seeking finance. BANs played an important role in financing innovative start-ups also in peripheral regions. Results lead us to conclude that government support BANs would appear to be an effective mechanism to stimulate the angel market in developing informal venture capital markets. The conclusions of this paper are likely to have relevance for countries where there is growing interest in the potential of business angels as a means of financing innovative start-ups.